“Didong” Art as Health Promotion to Improve Natural Disaster Awareness - Nur Asiah; Ryan Indrawan; Firman Parlindungan (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Didong is one of the cultural arts originating from the Gayo tribe of Bener Meriah, Takengon and Gayo Lues Regencies in Aceh Province, Indonesia. Furthermore, it is an art that combines movement, vocals and artistic literature to educate the public about government programs, such as health-care sector in the context of health promotion. The Bener Meriah regency experienced an earthquake in 2013, which result in the death of 14 people and 100 were injured. Therefore, this study aims to determine the didong art as a medium for health promotion, and the sample used were purposive sampling, which include the recitation group of 69 people. Also, a pre-experimental design with one shot case study was used. Furthermore, data was collection techniques include questionnaires, observation and interviews, and it was analyzed using percentage descriptive method to describe all varriables The community watched the didong art performance via video for 20 minutes, and subsequently an assessment was performed on the community. Based on the results, 85% of community groups stated that the didong art was used as a tool in health promotion in relation to the effect of natural disasters on public health. The art's unique local wisdom makes it easier for the community to understand the contents of didong art poetry, which contains messages regarding the impact of natural disaster in public health. In addition, the poetry was translated into Indonesia for easy understanding by people other than the Gayo tribe. Therefore, in order to determine the level of effectiveness in the use of didong art as promotion medium for public awareness about the effect of natural disaster, this research needs to be continued.